SEMANTIC AND PRAGMATIC IN TOBANESE WEDDING CEREMONY - Tiarnita Maria Sarjani Br Siregar; Dinda Khairani Pratiwi; Jose Sianipar; Laura Joyfebri R. Sitorus; Sherin Regina Raflesia Barus (Adisam Publisher, 2025)
Toba's customary marriage process is repetitive and complex. In the customary wedding procession of the Batak Toba, this has various stages where it becomes one of the things applied to honor the ancestors who have created it. This paper aims to analyze semantic and pragmatic studies of the process of customary marriage of the Batak Toba tribe. This research approach uses the process of studying documents by aggregating with the analysis of various documents, whether it is written documents, results of work, and so on. As for data analysis techniques using Miles and Huberman's theories of data reduction, presentation of data, and conclusion. The purpose of this work is to show the public some stages accompanied by procedures and meanings in semantics and pragmatism of the customary marriage process of Batak Toba. Every phase of the Batak Toba customary marriage contains sacred cultural values.